Autism in Preschoolers: Does Individual Clinician’s First Visit Diagnosis Agree with Final Comprehensive Diagnosis? - Gunilla Westman Andersson; Carmela Miniscalco; Christopher Gillberg (The Scientific World Journal)
Comprehensive clinical diagnosis based on all available information is considered the “gold standard” in autism spectrum disorders (ASD). We examined agreement across independent assessments (clinical judgment) of 34 young children (age 24–46 months) with suspected ASD, assessed by a multidisciplinary team, and final comprehensive clinical diagnosis. Agreement across settings and between each clinician’s assessment and final diagnosis was moderate. The poorest fit was found at assessment in connection with psychological evaluation and the best with preschool observation and parent interview. Some individual clinicians had good and others had poor fit with final diagnosis. Disagreement across assessments was pronounced for girls. The findings suggest that multidisciplinary assessments remain important and that comprehensive clinical diagnosis should still be regarded as the gold standard in ASD.